Optimal Control of Monkeypox Transmission Model with the Effect of Hospitalization - Inayaturohmat, Fatuh; Pramesti, Retta Farah; Pratama, Gilar Budi; Cahyani, Nita; Hanifah, Aisyah (Jurnal Matematika Integratif, 2025)
Monkeypox, also known as mpox, is a zoonotic illness caused by the Monkeypox Virus (MPV), which belongs to the Orthopoxvirus genus within the Poxviridae family. According to a WHO report as of September 2023, the virus has spread to numerous non-endemic countries, showing a significant number of cases. The United States reported the highest count, with 4,259 cases. In contrast, Indonesia has reported relatively fewer cases compared to other Southeast Asian nations. Nonetheless, the risk of transmission, particularly through close personal contact, remains a public health concern. This study examined the transmission of monkeypox among human populations using the spread model proposed by previous research. The novelty of this research is the enhancement of the model by introducing hospitalization parameters as a control mechanism, aiming to determine the optimal hospitalization level to minimize the disease's spread. The method used for optimal control is minimum pontryagin principle. The model also consider the asymptomatic and symptomatic infected individuals. There is a transition from asymptomatic to symptomatic individuals. Numerical simulation results show that implementing this control leads to a more rapid decline in the number of symptomatic infected individuals compared to scenarios without control measures.